In the still of the night : the strange death of Ronda Reynolds and her mother's unceasing quest for the truth - Rule, Ann. (New York : Free Press, 2010)
"From true-crime legend Ann Rule comes this riveting story of a young woman whose life ended too soon--and a determined mother's eleven-year crusade to clear her daughter's name"--Cover, p. 2.
Keywords: Reynolds, Ronda, -- 1965-1998.; Murder -- Washington (State) -- Chehalis -- Case studies; Murder -- Investigation -- Washington (State) -- Chehalis -- Case studies